Frontiers in fascia research. Issue 4 (October 2018) - Avila Gonzalez, Carla Alessandra; Driscoll, Mark; Schleip, Robert; Wearing, Scott; Jacobson, Eric; Findley, Tom; Klingler, Werner
Abstract: Basic sciences are the backbone of every clear understanding of how the body is composed and how different structures and functions are connected with each other. It is obvious that there is a huge variability in human beings - not only in terms of the outer appearance such as measurements of height, weight, muscle mass and other physical properties, but also with respect to metabolic and functional parameters. This article highlights recent developments of research activities in the field of fascia sciences with a special emphasis on assessment strategies as the basis of further studies. Anatomical and histological studies show that fascial tissue is highly variable in terms of density, stiffness, and other parameters such as metabolic and humoral activity. Moreover, it encompasses nerves and harbours a system of micro-channels, also known as the primo vascular system. As ultrasound is a widely available method, its use is appealing not only for imaging of fascial structures, but also for thorough scientific analysis. Unlike most other imaging technologies, US has the advantage of real-time analysis of active or passive movements. In addition, other assessment methods for fascial tissue are discussed. In conclusion, fascial tissue plays an important role not only in functional anatomy, but also in evolutionary and molecular biology, sport, and exercise science as well as in numerous therapeutic approaches. A high density of nerves is found in fascial tissue. Knowledge of individual characteristics, especially by visualizing with ultrasound, leads to personalized therapeutic approaches, such as in pain therapy.